Decoupled linear loan flow for contingency analysis/ Noraniza Mohamad Yusof - Mohamad Yusof, Noraniza (1996)
The load flow problem can be defined as the calculation_ of the real and reactive powers flowing in each line and the magnitude and phase angle of the voltage at each bus of a given transmission system for specified generation and load conditions. The information obtained from the load-flow studies can be used to test the system's capability to transfer energy from generation to load without overloading lines and to determine the adequacy of voltage regulation by shunt capacitors, shunt reactors, tap-changing transformers, and the var-supplying capability of rotating machines. From the introduction of digital load flow solution by Ward and Hale in 1956, many methods and many modifications and improvements have been proposed from time to time. The relative properties and performances of different load flow methods can be influenced substantially by the types and sizes of problems to be solved.